Tubuh yang Terlibat, Konteks, dan Objektivitas: Sains sebagai Praktik Sosial yang Manusiawi - Muhammad Nurul Huda; Amsar A. Dulmanan (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2024)
Dominant perspectives in modern science assume that scientific knowledge is ideally value-free and neutral. This claim is problematic as it overlooks the fact that science is a social practice carried out by knowers—embodied, context-bound, and value-laden beings. This article, through the lens of critical realism and personalism, offers an alternative framework that understands science as a value-laden activity without abandoning its commitment to objective reality. A philosophical analysis, combined with two historical case studies—Imam al-Shafi‘i’s revision of Islamic jurisprudence and Copernicus’ scientific revolution—yields three main findings. First, scientific knowledge is fallible, as it is rooted in the limitations of human conditions. Second, scientific objectivity is achieved not by eliminating values, but through critical reflection on the positionality of values within scientific communities. Third, a fully humanized science is more capable of generating transformative and responsible knowledge. These findings offer important implications for epistemology, education, and contemporary scientific practice, particularly in rethinking the relationship between reality, values, and the knowing subject.